Supramolecular Polymer Network‐Mediated Self‐Assembly of Semicrystalline Polymers with Excellent Crystalline Performance. Issue 5 (20th January 2017) - Cheng, Chih‐Chia; Chuang, Wei‐Tsung; Lee, Duu‐Jong; Xin, Zhong; Chiu, Chih‐Wei
Abstract : Functional supramolecular polymers can be used to manipulate the nucleation and growth processes of polymer crystals, resulting in substantially enhanced crystallization performance at an ultralow content of sextuple hydrogen‐bonded uracil‐diamidopyridine motifs. Abstract : A novel application of supramolecular interactions within semicrystalline polymers, capable of self‐assembling into supramolecular polymer networks via self‐complementary multiple hydrogen‐bonded complexes, is demonstrated for efficient construction of highly controlled self‐organizing hierarchical structures to offer a direct, efficient nucleation pathway resulting in superior crystallization performance. Herein, a novel functionalized poly(ε‐caprolactone) containing self‐complementary sextuple hydrogen‐bonded uracil‐diamidopyridine (U‐DPy) moieties is successfully developed and demonstrated excellent thermal and viscoelastic properties as well as high dynamic structural stability in the bulk state due to physical cross‐linking created by reversible sextuple hydrogen bonding between U‐DPy units. Due to the ability to vary the extent of the reversible network by tuning the U‐DPy content, this newly developed material can be readily adjusted to obtain the desired crystalline products with specific characteristics. Importantly, incorporating only 0.1% U‐DPy resulted in a polymer with a high crystallization rate constant, short crystallization half‐time, and much more rapid crystallization kinetics than pristine PCL, indicating a low content of U‐DPy moieties provides highly efficient nucleation sites that manipulate the nucleation and growth processes of polymer crystals to promote crystallization and chain alignment in bulk. This new system is suggested as a potential new route to substantially improve the performance of polymer crystallization.